The Mechanism of Rainfall-Induced Landslide Around Railway Tracks in Central Java Province, Indonesia - Octaviarini, Ika Sakti; Fathani, Teuku Faisal; Hardiyatmo, Hary Christady; Amalina, Anisa Nur; Erzagian, Egy (INERSIA lnformasi dan Ekspose Hasil Riset Teknik Sipil dan Arsitektur, 2023)
Landslide is one of the most disastrous natural hazards in Indonesia, causing significant fatalities and economic losses. Landslides can be triggered by several factors, such as rainfall, earthquakes, soil conditions, and others, where each landslide event has its own triggering and controlling factors. A progressive landslide occurred on the Central Java railway line which resulted in damage to the double-track railway as a transportation infrastructure. The objective of this paper is to understand the process and triggering factors of the landslide. Information was collected through field investigations and measurements based on drilling results at 3 points, geophysical surveys at 5 lines, and laboratory testing of several soil samples. Geological and geotechnical settings, topography, lithology, hydrogeology, and rainfall data of the area were analyzed. Aerial photographs and other remote sensing data were used to evaluate and discuss the information. Landslides in the study area occurred in stages, starting with the formation of a tension crack, followed by two landslides over five months. The results show that the clay material that dominates the study area is the dominant controlling factor of a landslide, triggered by long-duration, low-intensity rainfall. Rainwater entering through tension cracks increases moisture content, adding load to the slope and triggering landslides. Furthermore, the train's external load on the slope also contributes to the occurrence of landslides. The static and cyclic load of the train causes changes in the slope's pressure balance, generating a force that drives the downslope soil. Further analysis was performed using back analysis method with the limit equilibrium method to enhance understanding of slope stability parameters at the time of slope failure. The analysis was performed considering the rising groundwater level. A factor of safety (FS) value of 0.989 was obtained at the end of the simulation, indicating that the slope had failed.